Diseño de señalética en la Vía Vuelta Larga-Cone del cantón San Jacinto de Yaguachi, Ecuador - Bravo Murillo, María Elizabeth (2024)
A solid knowledge of traffic signs and road laws helps reduce accidents and increase safety on the roads. This work is divided into six chapters and the importance of an adequate road signaling system to ensure fluid and safe circulation is highlighted. The study is focused on the Vuelta Larga – Cone road, belonging to the Yaguachi canton, Ecuador, which faces road safety challenges due to population and economic growth. In particular, the lack of adequate signage, such as worn, vandalized or non-existent signs, and inconsistency in design and regulations, contributes to road insecurity. This work seeks to improve road signage on this second-order road to reduce accidents and protect users who travel along it, with a positive impact at both the local and provincial levels..........